PENGEMBAGAN MEDIA PEMBELAJARAN LEMARI KATA BERBASIS 3D TERHADAP KETERAMPILAN MEMBACA DIKELAS II SEKOLAH DASAR - Ade Ainun Nadilah; Rina Yuliana; Encep Andriana (Universitas Negeri Medan, 2023)
The goal of this study is to create word cabinet learning media for grade II SD reading skills based on 3D technology and to create word cabinet learning media that match the requirements for being practical to use in Indonesian language courses for grade II SD reading abilities. The problem analysis, data collecting, product design, design validation, design revision, and product testing constitute the research methodology that Sugiyono modified. Expert validation tests are performed by media experts, material experts, and language experts on this educational media. A product trial was conducted with the research subject, class II pupils at Panunggulan 3 Elementary School, after a validation test by a team of experts. The outcomes of the of student responses obtained an average score of 83% in the